Pengembangan Media Match Snail Adventure Berbasis Permainan Edukasi Software Macromedia Flash 8 Pada Mata Pelajaran Matematika Kelas 4 SD - Ary Kustiyani; Muhammad Mutofifin (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to develop an Interactive Match Snail Adventure learning media based on Macromedia Flash 8 Software Educational Game in 4th Grade Mathematics Subjects. The research method used is development research with research and data collection stages, initial product planning, product development, validation, revision, field trials, and product revisions. The results of this study indicate that the Interactive Match Snail Adventure learning media based on Macromedia Flash 8 Software Educational Learning in Mathematics for Grade 4 Elementary School is very feasible to be used in learning by teachers and students. Based on several stages of testing, the learning media is categorized as very feasible with a feasibility level of 90%. This research is expected to be a medium of learning in the subject matter of Waking Flat for 4th grade elementary school and can be useful for teachers, students, and advanced researchers.